Impact of a new general form of friction and thermal forces on SOLPS‐ITER modelling results. Issue 6 (1st February 2018) - Sytova, E.; Kaveeva, E.; Rozhansky, V.; Senichenkov, I.; Voskoboynikov, S.; Coster, D.; Bonnin, X.; Pitts, R.A.
Abstract : The SOLPS‐ITER transport code was released in 2015 on the basis of older versions of SOLPS and the EIRENE Monte Carlo code for neutrals. In the parallel momentum balance equations of this first release, each of the ion species was combined with the parallel momentum balance for electrons so as to eliminate the electric field term. In doing so, the expressions for the thermal and friction forces were approximated for simplification. Such approximations break down for multi‐component plasma modelling. It was subsequently proposed to return to solving the original (Braginskii) ion momentum balance equations, with the electric field term included, and with more accurate treatment of friction and thermal force terms, although the treatment of these terms still assumed trace impurities. In the present work, more general expressions for the friction and thermal forces, valid for high impurity densities ( z eff − 1 > 1 at the separatrix), are suggested. This new form for the force terms within the Braginskii equation has now been implemented in SOLPS‐ITER and has been tested through the use of simulation test cases of nitrogen‐seeded scenarios in ASDEX Upgrade geometry, with drifts and currents switched on. This paper discusses the effect of the new form of the terms in the Braginskii equation, emphasizing the differences with the trace impurity approach. It demonstrates that the latter already begins to fail in simulations for which z eff = 1.5. The influence of the transition from the old form of the momentum balance equation to the new general Braginskii formulation with corrected friction and thermal force terms is demonstrated by comparing SOLPS‐ITER ASDEX Upgrade simulations employing both descriptions.